2007
DOI: 10.1088/0953-8984/19/11/116105
|View full text |Cite
|
Sign up to set email alerts
|

Liquid polymorphism, density anomaly and H-bond disruption in associating lattice gases

Abstract: Abstract.We have investigated the effects of either distorting hydrogen bonds or removing proton degeneracy on the thermodynamic properties of a minimal model for associating liquids. The presence of two liquid phases and a density anomaly is unaffected in both cases. Increasing the degeneracy of bonded structures leads to lower temperature critical points and a steeper liquid-liquid coexistence line, implying a low density liquid of larger entropy.Analysis of the hydrogen bond net accross the phase diagram in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(64 citation statements)
references
References 36 publications
(42 reference statements)
10
50
2
2
Order By: Relevance
“…The physical motivation behind these studies is the assumption that two length scales systems exhibit the same anomalous behaviors present in water. Confirming this hypothesis a number of continuous [1][2][3][4][5][6][7] and lattice gas models [8][9][10][11][12][13][14][15][16] show the presence of density, diffusion, and structural anomalous behavior as observed in water [17,18].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…The physical motivation behind these studies is the assumption that two length scales systems exhibit the same anomalous behaviors present in water. Confirming this hypothesis a number of continuous [1][2][3][4][5][6][7] and lattice gas models [8][9][10][11][12][13][14][15][16] show the presence of density, diffusion, and structural anomalous behavior as observed in water [17,18].…”
Section: Introductionmentioning
confidence: 54%
“…By lowering T * , the λ line is crossed, which one sublattice is emptied and the others remaining filled with an reorganization of the inert arms that form the above ordered zig-zag structure. This the λ line transition is identified by the peak of the specific heat at constant volume c V [15].…”
Section: The Density Of Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Even though there are a number of two and three dimensional lattice models that would in principle exhibit the anomalies present in water, 6,16,[19][20][21] here water is represented by the associating lattice gas (ALG) (Refs. [22][23][24][25][26][27][28]) that has already shown the density and diffusion anomalies described above. The ALG does not have the full complexity of the molecular liquid, however it leads to a network-forming fluid in which directionality plays an important role.…”
Section: Introductionmentioning
confidence: 69%
“…It was also shown that the for the presence of the anomalies it is not relevant the distinction between the acceptor and donor arm in the hydrogen bond. 38 Which would be the contribution of the directionality in these models? In order to answer this question in this paper we explore thoroughly the properties of the Bell-Lavis model.…”
Section: Introductionmentioning
confidence: 99%